PERSONAL DATA PROTECTION FOR DEBTORS BY OTORITAS JASA KEUANGAN (OJK) AGAINTS ILLEGAL ONLINE LOANS IN INDONESIA - Nazwa Hawwa Audica (Law Research Review Quarterly, 2026)
Alongside the quick advancement of financial technology, protecting debtors' personal information in illicit internet lending activities has emerged as a critical legal concern in Indonesia. The primary problem lies in the widespread abuse of personal information and transgressions of consumer rights, the methodology Normative legal research using conceptual and statutory methodologies is employed. The purpose of this study is to assess how debtors' personal data is protected and to look at Otoritas Jasa Keuangan's (OJK) place in the current legal system. Statutory and conceptual methods for normative legal study is the methodology employed, analyzed descriptively through a literature study. The results indicate that. Normatively, personal data and consumer protection are regulated under various laws and regulations; however, inconsistencies between regulations remain, along with the limited authority of Otoritas Jasa Keuangan in reaching illegal online lending providers operating outside the formal supervisory system. This condition creates a gap between legal norms (das sollen) and field practices (das sein), resulting in suboptimal legal protection for debtors. These findings emphasize the need to strengthen an integrative legal approach through cross sector coordination, optimized supervision, and enhanced law enforcement to ensure legal certainty and protection for debtors within the digital financial services sector.